Resonant scattering of the O vii X-ray emission line in the circumgalactic medium of TNG50 galaxies - Nelson, Dylan; Byrohl, Chris; Ogorzalek, Anna; Markevitch, Maxim; Khabibullin, Ildar; Churazov, Eugene; Zhuravleva, Irina; Bogdan, Akos; Chakraborty, Priyanka; Kilbourne, Caroline; Kraft, Ralph; Pillepich, Annalisa; et al. (Monthly notices of the Royal Astronomical Society, 2023)
We study the impact of resonantly scattered X-ray line emission on the observability of the hot circumgalactic medium (CGM) of galaxies. We apply a Monte Carlo radiative transfer post-processing analysis to the high-resolution TNG50 cosmological magnetohydrodynamical galaxy formation simulation. This allows us to model the resonant scattering of  O vii(r) X-ray photons within the complex, multiphase, multiscale CGM. The resonant transition of the O vii He-like triplet is one of the brightest, and most promising, X-ray emission lines for detecting the hot CGM and measuring its physical properties. We focus on galaxies with stellar masses 10.0<log(M⋆/M⊙)<11.0 at z ≃ 0. After constructing a model for  O vii(r) emission from the central galaxy, as well as from CGM gas, we forward model these intrinsic photons to derive observable surface brightness maps. We find that scattering significantly boosts the observable  O vii(r) surface brightness of the extended and diffuse CGM. This enhancement can be large – an order of magnitude on average at a distance of 200 projected kpc for high-mass M⋆ = 1010.7 M⊙ galaxies. The enhancement is larger for lower mass galaxies and can even reach a factor of 100, across the extended CGM. Galaxies with higher star formation rates, AGN luminosities, and central  O vii(r) luminosities all have larger scattering enhancements, at fixed stellar mass. Our results suggest that next-generation X-ray spectroscopic missions, including XRISM, LEM, ATHENA, and HUBS – which aim to detect the hot CGM in emission – could specifically target haloes with significant enhancements due to resonant scattering.
Veröffentlicht: 21. April 2023
Gesehen am 26.07.2023